CORRELATION OF QANADLI SCORE WITH RIGHT VENTRICULAR DYSFUNCTION IN PATIENTS WITH ACUTE PULMONARY EMBOLISM - Zahoor, Anam; Khan, Nasir; Khan, Ghayyur (Pakistan Journal of Physiology, 2017)
Background: CT-pulmonary angiography (CTPA) is routinely performed in patients with suspected pulmonary embolism (PE) and a positive relationship between Qanadli score (Q-score) and RV-dysfunction enables the clinicians in early diagnosis and management of RV-dysfunction on the basis of this single imaging modality. Objective of the study was to determine the correlation between an established angiographic clot burden score (Qanadli score-QS) and parameters of right ventricular dysfunction (RVD) on CT pulmonary angiography in patients with acute pulmonary embolism. Methods: A Cross-sectional study was carried out for the period of six months from 16 Jun to 15 Dec 2016. Total of forty-six (46) patients of either gender aged 15–70 years with confirmed evidence of PE were recruited. The Q-score and parameters of RV-dysfunction (LV/RV, ratio, SVC diameter, AV-diameter and PA/Ao ratio) were calculated in each patient. Correlation between Q-Score and RV parameters were determined and binary logistic regression analysis was applied to assess Q-score as an independent predictor of RV-dysfunction. Results: Avery strong positive correlation was found between Q-score and LV/RV ratio (r>0.7, p<0.05) collectively and after gender and age based stratification. No significant correlation was found between Q-score and other RV parameters among both genders and age groups (p>0.05 in all cases). No independent factors were found to be significantly related to RV dysfunction after adjustment for other factors (p>0.05). Conclusion: Qanadli score on CT pulmonary angiogram correlates positively with indicators of right ventricular dysfunction of CT angiogram in patients with acute pulmonary embolism and confer a poor prognosis with higher scores. Pak J Physiol 2017;13(4):14–7